PRICE, BRAND EQUITY, AND PERCEIVED QUALITY ON PURCHASE INTENTION OF HONDA SCOOTER MOTORCYCLE IN MANADO - Siahaan, Marulitua C.; Pangemanan, Sifrid S.; Pandowo, Merinda (Universitas Sam Ratulangi, 2014)
The trend of using scooter motorcycles nowadays is crucial to support consumer daily activity; the increasing number of national whole sales shows a good sign for motorcycle industry, this research specialized explores the effect of three important variables that according to author gives significant effect on Purchase Intention of Honda scooter motorcycles in Manado, the three variables are: Price, Brand Equity, and Perceived quality. This research tried to prove that the three variables are the most suitable variables to explain consumer basic attitude on purchasing scooter motorcycle. Research method that had been used for this research is associative with multiple linear regression analysis technique. The population is Honda scooter users in Manado city and Primary data used Questioners base on sample size of this research which is 120 respondents. Secondary data collection which is used Journal, Internet, and Text book. The result of this research shows positive impact for these three variables which are Price, Brand Equity, and Perceived Quality generally give the significant influence for the Customer Purchasing Intention for Honda Scooter Motorcycle in Manado. Keywords: price, brand equity, perceived quality, purchase intention.